2021
DOI: 10.1038/s41398-021-01647-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial morphology is associated with respiratory chain uncoupling in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that is associated with unique changes in mitochondrial metabolism, including elevated respiration rates and morphological alterations. We examined electron transport chain (ETC) complex activity in fibroblasts derived from 18 children with ASD as well as mitochondrial morphology measurements in fibroblasts derived from the ASD participants and four typically developing controls. In ASD participants, symptoms severity was measured by the Social Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…There is growing evidence that mitochondrial dysfunction, which often correlates with mitochondrial fragmentation, is likely to contribute to ASD (Citrigno et al, 2020; Pecorelli et al, 2020; Rossignol & Frye, 2012; Singh et al, 2020; Thorsen, 2020; Weissman et al, 2008). For example, ASD patient cells (Barone et al, 2021; Frye et al, 2021; Gevezova et al, 2021) and brain organoids (Ilieva et al, 2022) exhibit impaired mitochondrial bioenergetics, while postmortem brains of control and ASD patients have increased expression of mitochondrial fission proteins and decreased expression of mitochondrial fusion proteins (Tang et al, 2013). This correlation is also present in animal models of ASD, as neuronal mitochondria in the BTBR mouse model of ASD have reduced mitochondrial function and are more fragmented (Ahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that mitochondrial dysfunction, which often correlates with mitochondrial fragmentation, is likely to contribute to ASD (Citrigno et al, 2020; Pecorelli et al, 2020; Rossignol & Frye, 2012; Singh et al, 2020; Thorsen, 2020; Weissman et al, 2008). For example, ASD patient cells (Barone et al, 2021; Frye et al, 2021; Gevezova et al, 2021) and brain organoids (Ilieva et al, 2022) exhibit impaired mitochondrial bioenergetics, while postmortem brains of control and ASD patients have increased expression of mitochondrial fission proteins and decreased expression of mitochondrial fusion proteins (Tang et al, 2013). This correlation is also present in animal models of ASD, as neuronal mitochondria in the BTBR mouse model of ASD have reduced mitochondrial function and are more fragmented (Ahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of mitochondrial metabolism biomarkers have been described with many being associated with core and associated ASD symptoms [ 71 ]. For example, alternations in electron transport chain complex activity derived from buccal tissue [ 72 ] and fatty acid oxidation been linked to ASD-specific symptoms on the SRS [ 73 ] and variations in mitochondrial morphology have been linked to both ASD-specific symptoms on the SRS and core ASD symptoms on the ABC [ 74 ]. Abnormalities in transmethylation and transsulfuration spanning the methylation and redox pathways may be diagnostic for ASD [ 70 ] and have been shown to be related to neurodevelopment as indexed by the VABS in several studies [ 75 , 76 ].…”
Section: Specific Factors To Address In Autism Spectrum Disordermentioning
confidence: 99%
“…Noteworthy, clinical studies have reported altered mtDNA copy numbers and deletions (130,(134)(135)(136)(137), mtDNA mutations (138,139), mitochondrial ETC deficits (134,136,140) and altered plasma levels of lactate, pyruvate, alanine, creatine kinase, glutathione-S-transferase and caspase 7 (138,141). Recent studies in ASC-derived lymphoblastoid cell lines (LCLs) showed significantly increased mitochondrial respiration and mitochondrial membrane potential as well as elevated activities of ETC complexes (142), while disruptions to mitochondrial bioenergetics, dynamics and morphology were observed in ASC-derived fibroblasts (143,144). This is supported by independent transcriptomic studies that have reported reduced expression of mitochondrial respiration genes in ASC brain tissue (145)(146)(147)(148).…”
Section: Mitochondrial Allostatic Loadmentioning
confidence: 99%